2004
DOI: 10.1002/jnr.20118
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine‐induced cell death in human oligodendroglial cell lines: I. Synergistic effects of IFN‐γ and TNF‐α on apoptosis

Abstract: Multiple sclerosis is a chronic inflammatory disease of the central nervous system. Myelin and oligodendrocytes are considered the major targets of injury caused by a cell-mediated immune response. There is circumstantial evidence that proinflammatory cytokines like tumor necrosis factor alpha (TNF-alpha) and interferon gamma (IFN-gamma) could have disease-promoting roles in multiple sclerosis (MS). In the present study, the cytotoxic effects of IFN-gamma and TNF-alpha on the human oligodendroglial cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 58 publications
2
76
0
2
Order By: Relevance
“…1A, cell viability was reduced time-dependently to 86.8 ± 5.8%, 56.4 ± 4.3%, and 33.8 ± 0.9%, respectively. As reported previously (8,9), the cytokines acted synergistically to elicit maximal cytotoxic effects. The pattern of cytokine-induced cell death was further confirmed by LDH release assay (Fig.…”
Section: Exosome-like Vesicles Released From Cytokine-treated Culturesupporting
confidence: 77%
See 2 more Smart Citations
“…1A, cell viability was reduced time-dependently to 86.8 ± 5.8%, 56.4 ± 4.3%, and 33.8 ± 0.9%, respectively. As reported previously (8,9), the cytokines acted synergistically to elicit maximal cytotoxic effects. The pattern of cytokine-induced cell death was further confirmed by LDH release assay (Fig.…”
Section: Exosome-like Vesicles Released From Cytokine-treated Culturesupporting
confidence: 77%
“…The cells were subcultured into either 60 mm dishes (0.8 × 10 6 /2 ml) or 24-well plates (0.3 × 10 5 /0.5 ml/well). After 2 days, the cultures were switched to serum-reduced medium (0.05% FBS) and exposed to the cytokines, TNF-, IFN- (100 ng/ml each), or their combination, in order to induce apoptosis as described previously (9).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…30 However, during this peak developmental period, preoligodendrocytes are sensitive to reactive oxygen, nitrogen species, and cytokines secreted by microglia. [31][32][33][34][35] Neonatal hypoxia-ischemia and neuroinflammation lead to the activation of astrocytes and microglia, which induces myelin deficiency, associated with long-term cognitive problems. 30,36 Similarly, pain also induces both oxidative stress and inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally Vollgraf, 1998, Mronga et al, 2004), IL-1β (Takahashi et al, 2003), TNFα (Selmaj and Raine, 1988, Buntinx et al, 2004, and AA have all been shown to damage cultured oligodendrocytes.…”
Section: Introductionmentioning
confidence: 98%